2005
DOI: 10.1016/j.bbalip.2005.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of mast cell degranulation by a novel ceramide kinase inhibitor, the F-12509A olefin isomer K1

Abstract: Antigen-induced degranulation of mast cells plays a pivotal role in allergic and inflammatory responses. Recently, ceramide kinase (CERK) and its phosphorylated product ceramide 1-phosphate (C1P) have emerged as important players in mast cell degranulation. Here, we describe the synthesis of a novel F-12509A olefin isomer, K1, as an effective CERK inhibitor. In vitro kinase assays demonstrated that K1 effectively inhibits CERK without inhibiting sphingosine kinase and diacylglycerol kinase. Treating RBL-2H3 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…In this regard, a recent report by Igarashi and coworkers (11,41) demonstrated that C1P induced the release of b-hexosaminidase from RBL-2H3 cells via CERK. The localization of CERK to the trans-Golgi apparatus is also in accordance with the report by Carre and coworkers (10), who reported that overexpression of CERK tagged with green fluorescent protein (not endogenous CERK) in COS-1 cells results in localization to perinuclear/Golgi membrane using a fluorescent ceramide as a Golgi marker.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a recent report by Igarashi and coworkers (11,41) demonstrated that C1P induced the release of b-hexosaminidase from RBL-2H3 cells via CERK. The localization of CERK to the trans-Golgi apparatus is also in accordance with the report by Carre and coworkers (10), who reported that overexpression of CERK tagged with green fluorescent protein (not endogenous CERK) in COS-1 cells results in localization to perinuclear/Golgi membrane using a fluorescent ceramide as a Golgi marker.…”
Section: Discussionmentioning
confidence: 99%
“…CerK biology is still poorly understood. The discovery that C1P could activate the cytosolic phospholipase A2 ␣ isoform (PLA2G4A) in A549 human lung adenocarcinoma cells (Pettus et al, 2003(Pettus et al, , 2004) stimulated a search for CerK inhibitors that might have anti-inflammatory properties (Kim et al, 2005;Munagala et al, 2007). However, despite significant progress in characterizing in vitro the interaction of C1P and PLA2G4A (Stahelin et al, 2007), evidence that a C1P-PLA2G4A interaction plays a role in the cell or in vivo is lacking.…”
Section: A Potent and Specific Ceramide Kinase Inhibitor 927mentioning
confidence: 99%
“…B-5354c, isolated from a novel marine bacterium, blocked the production of S1P and caused sphingosine to accumulate in sheep erythrocytes (Ochi et al, 2004). F-12509a, a sesquiterpene quinone isolated from a culture broth of the discomycete, Trichopezizella barbata SANK 25395, was shown to be a competitive inhibitor of SphK1 (Kono et al, 2000b;Kim et al, 2005). Although these natural products are moderately potent SphK inhibitors, the possibility of large-scale production remains unknown, and their synthesis seems impractical because of their complex structures.…”
Section: Sphingosine Kinase Inhibitorsmentioning
confidence: 99%